2010
DOI: 10.2353/ajpath.2010.090895
|View full text |Cite
|
Sign up to set email alerts
|

A Human-Type Nonalcoholic Steatohepatitis Model with Advanced Fibrosis in Rabbits

Abstract: Nonalcoholic steatohepatitis (NASH) progresses to liver fibrosis and cirrhosis, which can lead to lifethreatening liver failure and the development of hepatocellular carcinoma. The aim of the present study was to create a rabbit model of NASH with advanced fibrosis (almost cirrhosis) by feeding the animals a diet supplemented with 0.75% cholesterol and 12% corn oil. After 9 months of feeding with this diet, the rabbits showed high total cholesterol levels in serum and liver tissues in the absence of insulin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 62 publications
(84 reference statements)
6
42
0
Order By: Relevance
“…Accordingly, hepatic gene expression analysis indicates that markers of stellate cell activation (such as aSMA), fibrosis (such as TIMP1) and inflammation (such as TLR2 and TLR 4, the M1 macrophage marker CD68, and several chemokines and cytokines) were all markedly up-regulated in MetS rabbit livers. Our results are in keeping with other models of HFD-induced steatohepatitis in rabbits (Ogawa et al, 2010). Interestingly, the vast majority of these hepatic genes were negatively related to penile responsiveness to Ach.…”
Section: Discussionsupporting
confidence: 77%
“…Accordingly, hepatic gene expression analysis indicates that markers of stellate cell activation (such as aSMA), fibrosis (such as TIMP1) and inflammation (such as TLR2 and TLR 4, the M1 macrophage marker CD68, and several chemokines and cytokines) were all markedly up-regulated in MetS rabbit livers. Our results are in keeping with other models of HFD-induced steatohepatitis in rabbits (Ogawa et al, 2010). Interestingly, the vast majority of these hepatic genes were negatively related to penile responsiveness to Ach.…”
Section: Discussionsupporting
confidence: 77%
“…In a 2-year open study, ezetimibe (10 mg/day) reduced serum insulin, HOMA-IR and serum cholesterol fractions in 45 NASH patients [20]. In C57Bl/6J mice [21] and rabbits [22] fed an HF and high cholesterol diet, ezetimibe improved hepatomegaly and liver injury. The dose of ezetimibe used here (5 mg/kg/day) is at the lower end of the range (5-20 mg/kg/day) used by others [21,23].…”
Section: Discussionmentioning
confidence: 97%
“…Values represent means±SD obtained from 8 rats, Means in the same row followed by the same letters do not differ significantly, and when the means followed by different letters differ significantly at (p ≥ 0.01) Also, the reduced effect of plasma lipid profile levels can be correlated with common carp and African catfish oils with a significant content of fatty acids EPA, DHA (omega-3 family), it is possible to confirm the previous recommendations of [54][55][56] who emphasized that omega-3 fatty acids play an important role in reducing the risk of atherosclerosis caused by elevated blood lipids. The data in the table (4) showed that CCO group has better reduction in TGs, TC, LDL-c, TC/HDL-c and TGs/HDL-c ratios than ACO group, which may be due to the high content of oleic, linoleic acids in common carp oil compared with African catfish oil.…”
Section: Impact Of Common Carp and African Catfish Oils Supplementatimentioning
confidence: 94%
“…Excess fats in our diets are a major source of cardiovascular diseases, atherosclerosis, obesity and fatty liver [1][2][3][4][5][6]. Many previous studies have confirmed that dieting play an important role in lowering blood lipids and reducing the harmful effects of saturated fat and cholesterol [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%